CALCULATION OF COOLING LOAD IN COLD STORAGE FOR CATCH STORAGE - Tumpu, Mula; Putra, Moh. Nurhabibie Eka; Siahaan, Juniawan Preston; Abrori, M. Zaky Latief; Demeianto, Bobby; Haris, Dendi (Politeknik Kelautan dan Perikanan Dumai, 2024)
This study aims to calculate the cooling load required in Cold Storage to store fish catches. Cold Storage is an important facility in the fisheries industry to maintain the quality and freshness of the product. Accurate cooling load calculation is essential to design an efficient and energy-saving refrigeration system. The methodology used includes data collection on Cold Storage specifications, environmental conditions, and characteristics of the stored products. The cooling load is calculated by considering factors such as transmission loads through walls, roofs, and floors; product loads; air infiltration loads; internal loads from lights, equipment, and personnel; and other loads. The calculation results show that the total cooling load for Cold Storage with a certain capacity is 17.68 kW. Sensitivity analysis was conducted to evaluate the effect of various parameters on the cooling load. This study also provides recommendations for optimizing Cold Storage design and operational strategies to improve energy efficiency. The results of this study can be used as a reference in designing and operating Cold Storage for more effective and economical storage of fish catches.